Análise dos assentamentos de Júlio de Castlhos/RS: implicações sociais, ambientais e a qualidade de vida dos assentados - Petry, Deoclécio Gomes (2014)
The overall objective of this dissertation was to analyze the settlements Ramada, Alvorada and Santa Júlia of MST in Júlio de Castilhos, Rio Grande do Sul and its social implications, environmental and quality of life of settlers. The methodology applied to this study was guided by the completion of a study of descriptive and applied nature, with the use of mixed research methodology, qualitative and quantitative, to outline the collection, description, and analysis of data. The methodology applied to this study was guided by the completion of a study of descriptive and applied nature, with the use of mixed research methodology, qualitative and quantitative, to outline the collection, description, and analysis of data. The mixed method answered the need to understand the relationship between certain variables and to qualitatively explore aspects of research issue being studied. Based on the use of mixed-method, the procedure for the removal of the questions was descriptive, with the technique of data collection by questionnaires. The results obtained, it can be concluded that all the specific objectives Identify the perception and concern of the settlers as the use of natural resources in the settlements; identify the profile of the settlements of the municipality of Júlio de Castilhos (Ramada, Alvorada e Santa Júlia); check for difference between the profile of the three settlements that are part of this study; identify social, environmental implications; identify the quality of life of the settlers) have been met and that the quality of life of the settlers who participated in the survey, the item with higher representativeness was personal relationships (89.54%), followed by Spirituality, religion and personal beliefs (88.56%) and the lowest was financial resources with 0.98%. With respect to the distribution of items according to the fields, through factor analysis, it can be concluded that the domain with greater participation in the explanation of the variability of the items was the PHYS (physical) with 21.181% followed by the PSYCH (Psychological) with 12.678% from 10.71% of SOCIAL ENVIR (environment) with 6.99% and Auto-evaluation of the quality of 5.85%.